Two “M”s in the North: Montanelli and Malaparte in Finland - Sciacovelli Antonio (Poland, 2025)
Indro Montanelli (1909–2001) and Curzio Malaparte (1898–1957) were in Finland during
World War II, the former as a witness (and envoy) of the “winter war” fought against the
Soviet Union by Finland (which had won independence from Russia in 1917), the latter
in the years of the “war of continuation”, when hostilities between the two countries
continued in the more complex picture of the second phase of the conflict, that is, after
Germany had attacked the Soviet Union. Most of their correspondence and annotations,
collected in volume, immediately became, for many readers, the representation of an
unequal clash between the small but well-prepared army of Finland (David) and the
populous ranks of the Red Army (Goliath). In this article, Antonio Sciacovelli highlights,
on the basis of his analysis of their writings, how their images of the Finns, the environment
and the particular situation of those years were conveyed to Italian readers, in the
“story” of the war events.